2022
DOI: 10.1111/jfbc.14450
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomics‐based identification of an antimicrobial peptide derived from goat milk fermented by Lactobacillus rhamnosus ( C25 )

Abstract: Antimicrobial peptides (AMPs) are emerging as promising novel drug applicants. In the present study, goat milk was fermented using Lactobacillus rhamnosus C25 to generate bioactive peptides (BAPs). The peptide fractions generated were separated using ultrafiltration membranes with molecular weight cut‐offs of 3, 5, and 10 kDa, and their antimicrobial activity toward Gram‐positive and Gram‐negative bacteria was investigated. Isolated AMPs were characterized using RP‐HPLC and identified by LC–MS/MS. A total of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 79 publications
3
5
0
Order By: Relevance
“…This suggests that the hydrolysates produced peptides with varying hydrophobicity and molecular weight, as observed in previous studies conducted by Kamal et al (2018) and Mudgil et al (2018). In a separate study by Iram, Kindarlae et al (2022), it was found that hydrolysis of goat milk by Lactobacillus rhamnosus (C25) resulted in small peak retention times on RP‐HPLC, ranging from 5 to 30 min, as previously reported by Panchal et al (2020). The chromatograms of both CPH and WPH peptides showed the presence of peaks across areas with retention times ranging from 5.31 to 24.21 min.…”
Section: Resultssupporting
confidence: 63%
“…This suggests that the hydrolysates produced peptides with varying hydrophobicity and molecular weight, as observed in previous studies conducted by Kamal et al (2018) and Mudgil et al (2018). In a separate study by Iram, Kindarlae et al (2022), it was found that hydrolysis of goat milk by Lactobacillus rhamnosus (C25) resulted in small peak retention times on RP‐HPLC, ranging from 5 to 30 min, as previously reported by Panchal et al (2020). The chromatograms of both CPH and WPH peptides showed the presence of peaks across areas with retention times ranging from 5.31 to 24.21 min.…”
Section: Resultssupporting
confidence: 63%
“…Moreover, Iram et al [ 118 ] and Liu et al [ 119 ] reported that L. fermentum , L. pentosus , and L. acidophilus , which were isolated from human milk, fruits, milk products, and fermented shrimps in Malaysia, have the ability to produce cell-free biosurfactants that exhibit antibacterial properties. Haakensen et al [ 120 ] identified Pediococcus dextrinicus SHU1593 as another bacterium capable of producing biosurfactants.…”
Section: Antimicrobial Properties Of Microbial Biosurfactantsmentioning
confidence: 99%
“…For example, most predominant plasmin (secreted in milk as plasminogen) causes proteolysis of α S1 -CN, α S2 -CN, and β-casein (β-CN) into γ-CN [50], and it can have beneficial or detrimental results depending on the extent of hydrolysis [51]. Further, hydrolysis of milk proteins and release of bioactive peptides can occur via various processes, for example, naturally, by digestive enzymes and/or microbial enzymes, by enzymatic hydrolysis in laboratories [3,52], and by fermentation of milk [32]. After protein hydrolysis, the bioactive peptides are isolated and validated for their activities.…”
Section: Milk Proteins/peptidesmentioning
confidence: 99%
“…Peptidomic-based analyses have been carried out to search for the peptides with potential antimicrobial activities. The goat milk was fermented by Lactobacillus rhamnosus C25 (2%) at 37 • C for 48 h [32] to generate the peptides from milk proteins. The peptides were subjected to ultrafiltration with the MWCO membranes of 3, 5, and 10 kDa, and each resulting peptide fraction was evaluated for microbial activities against gram-positive/negative bacteria.…”
Section: Milk Proteins Protein-derived Peptides and Hydrolysatesmentioning
confidence: 99%
See 1 more Smart Citation